2022
DOI: 10.1136/openhrt-2021-001937
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of oral P2Y12inhibitors after non-ST-elevation acute coronary syndromes: a network meta-analysis

Abstract: BackgroundCurrently, potent P2Y12 inhibition with the use of prasugrel or ticagrelor is the mainstay of treatment after an acute coronary syndrome (ACS). The 2020 European Society of Cardiology (ESC) Guidelines recommend the use of prasugrel over ticagrelor in patients with non-ST-elevation ACS (NSTE-ACS) intended to receive invasive management (class IIa recommendation), however there are contradictory views regarding this recommendation.AimTo compare oral P2Y12 inhibitors in NSTE-ACS in terms of efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(87 reference statements)
1
2
0
Order By: Relevance
“…Our study results are also in agreement with the metanalysis published by Farmakis IT et al in patients of NSTEMI treated with P 2 Y 12 inhibitors which supports the use of prasugrel over ticagrelor as a more efficient strategy [28]. So we feel that for patients undergoing a pharmacoinvasive strategy following successful thrombolysis, prasugrel should be preferred over ticagrelor if patients have no contraindication to therapy with prasugrel.…”
Section: Discussionsupporting
confidence: 92%
“…Our study results are also in agreement with the metanalysis published by Farmakis IT et al in patients of NSTEMI treated with P 2 Y 12 inhibitors which supports the use of prasugrel over ticagrelor as a more efficient strategy [28]. So we feel that for patients undergoing a pharmacoinvasive strategy following successful thrombolysis, prasugrel should be preferred over ticagrelor if patients have no contraindication to therapy with prasugrel.…”
Section: Discussionsupporting
confidence: 92%
“…1 ). 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 From these systematic reviews, we identified 6 relevant RCTs. 14 , 24 , 25 , 26 , 27 , 28 We updated the search strategy from the most recent and comprehensive systematic review 15 to November 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Farmakis et al. 23 found that, in non ST-elevation-ACS patients, prasugrel-based DAPT is more efficacious than ticagrelor-based DAPT, whereas Fong et al. 21 found that, in ACS patients, prasugrel- and ticagrelor-based DAPT had a similar efficacy as ticagrelor-based DAPT.…”
Section: Discussionmentioning
confidence: 99%